2021
DOI: 10.4085/1062-6050-0494.20
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Administrators' Reporting of Emergency Preparedness Regarding Policies and Procedures in Iowa Secondary Schools

Abstract: Context: Secondary schools that offer school-sponsored athletic events should follow best-practice guidelines to provide policies that promote student health and safety. Objective: To assess emergency preparedness from the perspective of athletic administrators (AAs) in [State] secondary schools. Design: Cross-sectional study. Setting: Online survey. Patients or Other Participants: Ninety-eight AAs from [State] completed the survey (age=45.33 ± 10.22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…21 Despite this statement and guidelines, the majority of schools did not have (28%) or did not know if they had (36%) an emergency response plan. Previous studies have shown a number of barriers to implementing an emergency response plan including knowledge of how to implement a plan, 22,23 lack of funding, [22][23][24][25] lack of medical personnel. 24,25 One potential way to ameliorate the lack of medical personnel is the use of athletic trainers.…”
Section: Cardiology In the Youngmentioning
confidence: 99%
“…21 Despite this statement and guidelines, the majority of schools did not have (28%) or did not know if they had (36%) an emergency response plan. Previous studies have shown a number of barriers to implementing an emergency response plan including knowledge of how to implement a plan, 22,23 lack of funding, [22][23][24][25] lack of medical personnel. 24,25 One potential way to ameliorate the lack of medical personnel is the use of athletic trainers.…”
Section: Cardiology In the Youngmentioning
confidence: 99%